The Effect of Referral Process and Complications to Maternal Mortality - Indah Handriani; Soenarnatalina Melaniani (Jurnal Berkala Epidemiologi, 2015)
Maternal Mortality Rate (MMR) in East Java is still high. In 2013, MMR of Sidoarjo District reached 96.27 per 100,000 live births. The aim of this research is to analyze the effect of the referral process and complications on maternal mortality in the Regional Public Hospital (RSUD) Sidoarjo is an observational analytic study with a case-control approach. The case sample consisted of 25 pregnant women who were referred and experienced death and a control sample of 50 pregnant women who were referred and did not die. Data collection techniques using secondary data from the Maternal Neonatal Emergency (MNE) register and medical records and interviews with the respondent's mother or family or husband. Data were analyzed using univariable analysis, bivariable analysis, and multivariable analysis with logistic regression tests. The analysis shows that the referral process is not good (OR = 3,551; 95% CI: 1,258-10,027; p = 0,017) and pregnant women who have complications (OR = 147,429; 95% CI: 17,105-1270,702; p = 0,000) affect the incidence of maternal death. The conclusion of this study is the process of referral and complications affecting maternal mortality. Midwives need to improve referral quality and monitor high risks also provide health education for women of childbearing age, increase the participation of families, communities, and cadres in the early detection of complications during pregnancy, childbirth, and puerperal, and improve the quality of antenatal care.